2021
DOI: 10.3389/fgene.2020.615378
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of a Cis-Acting lncRNA in Non-small Cell Lung Cancer May Control HMGA1 Expression

Abstract: BackgroundLong non-coding RNAs (lncRNAs) have long been implicated in cancer-associated phenotypes. Recently, a class of lncRNAs, known as cis-acting, have been shown to regulate the expression of neighboring protein-coding genes and may represent undiscovered therapeutic action points. The chromatin architecture modification gene HMGA1 has recently been described to be aberrantly expressed in lung adenocarcinoma (LUAD). However, the mechanisms mediating the expression of HMGA1 in LUAD remain unknown. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Homology analysis showed that there were nine DELs with the same amino acid sequences as miRNA precursors and may correspond to miRNA precursors ( Supplementary Table S3 ). lncRNA also has a potential cis -regulatory capacity for adjacent coding genes ( 34 , 35 ). After the prediction of DEL cis -target genes ( Supplementary Table S4 ), statistics from KEGG annotation found that the top potential target gene-enriched terms were involved in GABAergic synapse ( Figure 5C ), which may promote the expression and secretion of gonadotropin signaling molecules ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homology analysis showed that there were nine DELs with the same amino acid sequences as miRNA precursors and may correspond to miRNA precursors ( Supplementary Table S3 ). lncRNA also has a potential cis -regulatory capacity for adjacent coding genes ( 34 , 35 ). After the prediction of DEL cis -target genes ( Supplementary Table S4 ), statistics from KEGG annotation found that the top potential target gene-enriched terms were involved in GABAergic synapse ( Figure 5C ), which may promote the expression and secretion of gonadotropin signaling molecules ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cis -regulatory effects of lncRNAs on neighboring genes have been well-examined ( 30 , 35 ). In this study, 136 cis -genes of DELs overlapped with DEMs, and 139 paired DELs and cis -genes had the same expression trends.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Stewart et al, high mobility group A1 (HMGA1) was implicated in tumorigenesis. HMGA1 has recently been described as an chromatin architecture modification gene and was found to be aberrantly expressed in LUAD 30 . The oncogenic role of high mobility group A (HMGA) proteins stems from chromatin‐mediated activation of cancer‐driving genes such as E2F transcription factor 1 (E2F1), Activator protein‐1 (AP1), and Cyclin A1 (CCNA1), as well as the repression of tumor suppressive genes such as TP53 31 .…”
Section: Discussionmentioning
confidence: 99%
“…HMGA1 has recently been described as an chromatin architecture modification gene and was found to be aberrantly expressed in LUAD. 30 The oncogenic role of high mobility group A (HMGA) proteins stems from chromatin-mediated activation of cancer-driving genes such as E2F transcription factor 1 (E2F1), Activator protein-1 (AP1), and Cyclin A1 (CCNA1), as well as the repression of tumor suppressive genes such as 31 Moreover, the expression of noncoding genes, such as miRNAs, has been proved to be affected by the overexpression of HMGA proteins, leading to lung development through dysregulation of the cell cycle. 32 In summary, these mRNAs are closely related to the regulation of inflammatory and hypoxia responses, regulation of artery smooth muscle cell proliferation and apoptosis, the response to the redox state, and the Bone morphogenetic protein (BMP) signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the function of lncRNAs, the cis-target genes of lncRNAs were predicted. lncRNAs may serve a cis role acting on neighboring target genes ( 49 , 50 ). A total of 100,000 up- and downstream coding genes were selected by Python Script ( ccb.jhu.edu/software/stringtie/ ) ( 51 ).…”
Section: Methodsmentioning
confidence: 99%